Quasi-marital (actual marital) relations: on the issue of the timeliness of legislative recognition - Zhunussova, T.B. (Bulletin of the Karaganda University “Law Series”, 2022)
Due to the significant increase in recent years of cases of cohabitation of a man and a woman without state registration of marriage, the issue of the legal regime of quasi-marital (actual marriage) relations and the possibility of its partial (or complete) equalization with the legal regime of official marriage is inevitably put on the agenda of legislative initiatives and theoretical justifications. The author presents the rationale for the definition of “quasi-marital relations”, which can be an optimal model instead of the terms “cohabitation”, “actual marital relations”, “civil marriage”, as having certain defects. The signs of actual marital relations identified in the doctrine of family law are considered. The experience of the Russian legislative initiative is studied. The statistical data of the conclusion and dissolution of marriage in Kazakhstan, the results of a sociological survey on the subject of the perception of the Kazakh population of quasi-marital relations are analyzed. The lack of a solution to this issue in Kazakhstan and most neighboring countries is an example of insufficient dynamism of legislation that lags behind social realities and trends. According to the author, the expediency of legislative “concessions” in favor of quasi-marital relations is largely due to the need to regulate traditional and alternative forms of marriage and family relations, the specifics of private law and public law issues.